Performance of Socially Responsible Investing During Financial Crisis: Evidence from 2008 crisis - Warell, Roope (My University, 2025)
Socially responsible investing (SRI) integrates environmental, social, and governance (ESG) factors into investment decisions and has gained attention as an alternative to traditional investing strategies. The performance and resilience of SRI during market turndowns and in general stable periods remain a topic of debate, as there is a lack of consensus regarding the performance of SRI against conventional methods. The purpose of this study is to examine whether SR indices, such as MSCI KLD 400 Social and MSCI USA SRI outperformed the market portfolio S&P 500 during the financial crisis of 2008. In addition, this thesis aims to provide evidence whether these SRI investments could provide a better hedge for investors against market crashes or even act as a safe haven. Performance differences are measured and discussed with ratios such as Sharpe and Treynor and regression models Jensen’s alpha, CAPM, and Fama-French 3-factor. The study focuses on the financial crisis of 2008 and time period used in data is from 15.9.2008 to 30.9.2009, which is commonly used window for the crash. Used data is from well known sustainable indices, MSCI KLD 400 Social and MSCI USA SRI. Benchmark index in the study is market index S&P 500 and data frequence in the study is daily. Log returns are calculated from sample indices’ daily total returns. Sources for data are Datastream and Kenneth R. French data library. The empirical results of the study suggest that there are no significant performance differences between SRI portfolio and conventional portfolio and using sustainable investing strategies does not provide a better hedge against the market downturns. Study finds that multiple results from regression models are statistically insignificant and no concluding evidence of overperformance hypothesis can be found either from regression models or from performance measures. Insufficient evidence can be partly explained by narrow dataset, therefore further studies should focus on comparing different time periods, using modern SRI funds and study other market events globally.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance